Bibliometric Study of Bureaucratic Culture, Leadership, and Educational Psychology in ASEAN (2010–2024) - Syafii, Muhammad Hisyam; Aladaya, Rudyn; Hamidah, Nurlaela (Center for Maritime Policy Governance Studies (CMPGS), 2025)
This study offers a thorough bibliometric examination of scholarly articles concerning bureaucratic culture, leadership, and educational psychology in the ASEAN area from 2010 to 2024. The study examines the necessity for a comprehensive comprehension of the intellectual framework and knowledge architecture in various interrelated domains within the Southeast Asian educational milieu. This work employed a quantitative bibliometric methodology to systematically examine scientific output from several databases, including Web of Science Core Collection, Scopus, and Google Scholar. The methodology utilized performance analysis, scientific mapping, and visualization tools such as Three-Field Plot, Reference Publication Year Spectroscopy (RPYS), theme mapping, and keyword co-occurrence network analysis. The findings indicate notable trends in research development, demonstrating that the literature is predominantly shaped by Western theoretical frameworks, especially from the United States, with few contributions from ASEAN nations despite the regional emphasis. The study highlighted fundamental themes including organizational culture, human behavior, and psychological components, while emergent subjects such as wellness, empowerment, and organizational justice signify current research trajectories. The study illustrates a transition from individualistic methods to a more systemic and contextual comprehension of psychological dynamics inside educational organizations. These findings offer significant insights for researchers, policymakers, and educational practitioners in ASEAN nations, emphasizing opportunities for enhanced regional collaboration and the incorporation of local cultural perspectives into global academic discussions on educational leadership and organizational psychology.